Notes on the historical conceptual streams for mathematics and physics teaching - Pisano, Raffaele (Lietuvos matematikos rinkinys, 2013)
Based on recent researches of mine concerning history and epistemology of sciences (physics and mathematics) one side and foundations of sciences within my physics and mathematics teaching other side, in this paper I briefly discuss and report the role played by history of science within physics and mathematics teaching. Some case-study on the relationship between mathematics, physics and logics in the history and teaching process are presented, as well.